Pro Nagios 2.0 - Turnbull, James (Apress : Imprint: Apress, 2006)
Pro Nagios 2.0 explains how to install and administer Nagios, the web-based enterprise management tool that helps monitor Unix, Windows, network devices, infrastructure equipment, and applications. You'll learn how to architect Nagios installations, deploy agents and plug-ins, and monitor a variety of assets, which include applications across a variety of platforms and operating systems. Nagios has the power to alert you to current and future incidents that could impact the availability, performance, and security of monitored assets. The books real-world configurations and supporting materials will enable you to deploy Nagios and integrate other tools (like MRTG and Snort) on a helpful step-by-step basis. Integrating Nagios with a variety of other tools can add more functionality to its internal monitoring and alerting capabilities. The book covers additional topics like security, redundancy and failover, and plug-in development. And it shows you how to create your own Nagios plug-ins, to monitor devices for which Nagios may not provide plug-ins.